Global Liquidity and Asset Prices : Measurement, Implications, and Spillovers - Baks, Klaas (IMF Working Papers; Working Paper ;, 1999)
Much recent commentary suggests that global liquidity has influenced financial conditions in the major international markets to an important degree, and that excess liquidity in one financial center can influence financial conditions elsewhere. Little formal research has addressed these issues, however. In this paper, we use three indexes of liquidity (money growth) in the Group of Seven industrial countries to explore the international dimension of the relationship between liquidity and asset returns. Evidence suggests that an increase in G-7 liquidity is consistent with a decline in G-7 real interest rates and an increase in G-7 real stock returns. There is also evidence of liquidity spillovers across countries.